Identification of the Diversity of Medicinal Plants Used by Battra in North Bengkulu - Kiki Fanisah; Iwan Setiawan; Deni Parlindungan; Bhakti Karyadi; Aprina Defianti; Ariefa Primair Yani (Postgraduate, University of Mataram, 2023)
All kinds of plants that are found in nature and have medicinal properties are considered medicinal plants. Utilization of medicinal plants can be used directly and mixed. Battra is a person who has knowledge of traditional medicine and is capable of concocting medicinal plants. North Bengkulu is one of the districts that still use conventional medical care. Utilizing medicinal plants that are proven to be able to treat those derived from natural ingredients can be healthful because of very few side effects compared to drugs that contain chemicals. The goal of the study was to catalog the various medicinal herbs used by Battra North Bengkulu. This study used 10 respondents' interviews as its approach. Battra uses 64 species from 37 families of medicinal plants as traditional medicinal ingredients. The most common type of family is Fabaceae. The habitus group that is widely used is 45% trees. Types of diseases that are commonly treated traditionally using these plants include fever, toothache, itching, cramps, internal heat, scales, stomach pain, malaria, long-term fever, colds (cholera), ulcers, lungs, kidney stones, jaundice, high blood pressure, appendicitis, fussy children, eye disease, intestinal worms, kesapo, sprains, tumors and gout. In the processing of medicinal plants by Battra in North Bengkulu, 11 processes the highest drug processing method was by boiling as much as 37%.